Learning to land: Basis of ACL protection for tennis - Petersen, C. (Medicine and Science in Tennis, 2010)
The anterior cruciate ligament (ACL) is a commonly injured knee ligament in tennis players. Knee injuries are a regular occurrence in ground based sports and injuries to the ACL are cause of prolonged absence from sports activity. Approximately 150,000 ACL injuries occur in the United States each year. The ACL is extremely important to tennis players as it serves a "crucial" function not only in preventing the tibia from sliding forward on the femur but in controlling rotation in the knee, thus preventing it from buckling when twisted or rotated during tennis training and competitive play. There are specific limitations associated with complete isolated ACL rupture, including subjective tennis performance impairment, limitations landing after a smash, stopping and changing step direction, difficulties playing a three set singles match, and playing on hard court surfaces. Tennis movements include sprinting, side-to-side running, cutting, twisting, sliding, and quick stops and starts. If the alignment, balance control, core stability and deceleration strength required to carry out these maneuvers is not optimal the knee can be at risk of injury. ACL tears may occur in isolation or in combination with associated injuries, particularly meniscal and articular cartilage injury, or injury to the MCL. Individuals who suffer an ACL injury and undergo surgery face a long rehabilitation process that can take 6 to 12 months. Surgical intervention does not always ensure a return to previous levels of activity. The majority of those who have ACL reconstruction have good to excellent knee function and most (65-88%) are able to return to sport within the first year. Among patients treated non-operatively, the return rate ranges from 19 to 82%.8,9 Even if the ACL is repaired it appears that you may have an increased risk of developing osteo-arthritis (OA) later in life. Nearly all patients undergoing modern ACL repair develop radiological signs of OA after 15-20 years. This is thought to be exacerbated by associated meniscal injury and bone bruising associated with articular cartilage damage that occurs in many ACL tears. ACL injuries account for a large health care cost estimated to be over half-billion dollars each year. Therefore trying to protect against injuries to the ACL should be part of every tennis players training program.